(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
No matter how much we write about the language, vocabulary, punctuation of Alisher Navoi, who skillfully uses the vocabulary, there are other aspects that we do not know. Navoi’s linguistic world is so vast and boundless that no matter how carefully and diligently the seeker acts, he cannot fully comprehend it. It is no exaggeration to say that the study of Alisher Navoi’s works, acquaintance with his mysterious linguistic world begins in small classes of schools of our country, is the basis for the deep absorption of Navoi’s works and words into our hearts. I also read Alisher Navoi’s poems at school for the first time. Undoubtedly, the magical melody, beautiful metaphors and unique rhymes of these poems inspired me to collect and analyze the rare gems of the Uzbek language from the ocean of Uzbek literature.